2015
DOI: 10.1016/j.lungcan.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The performance of a novel amino acid multivariate index for detecting lung cancer: A case control study in Korea

Abstract: These results suggest that the amino acid multivariate index previously developed from a Japanese dataset has the potential to aid in the early detection of lung cancers of different histological types in Korean patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
7
37
1
Order By: Relevance
“…The class of metabolites, which is currently the most explored in blood of NSCLC patients, is free amino acids. Some targeted metabolomic profiling focusing on determination of free amino acid levels in NSCLC has appeared in recent years (Klupczynska et al 2016a; Kim et al 2015; Shingyoji et al 2013; Maeda et al 2010). The analyses of amino acid profiles did not reveal one specific molecule that can play a role of NSCLC marker, but they emphasized the potential of using a multi-marker panel in lung cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…The class of metabolites, which is currently the most explored in blood of NSCLC patients, is free amino acids. Some targeted metabolomic profiling focusing on determination of free amino acid levels in NSCLC has appeared in recent years (Klupczynska et al 2016a; Kim et al 2015; Shingyoji et al 2013; Maeda et al 2010). The analyses of amino acid profiles did not reveal one specific molecule that can play a role of NSCLC marker, but they emphasized the potential of using a multi-marker panel in lung cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…The AICS™ test is currently performed to detect 7 types of cancers, and the AICS (lung) test for lung cancer is widely used in health and cancer screening in Japan. Several promising studies on similar or the same concepts have been reported abroad [5,21,22,24,25]. According to our previous ndings [1,8,9], this test may be an optional tool for the early detection of lung cancer, regardless of the tumor stage or progression, in contrast to other tumor markers, such as serum CEA and CYFRA.…”
Section: Discussionmentioning
confidence: 63%
“…The pathological changes in lung tissues were assessed by decreased lung metabolism via depletion of argenine, cysteine, glutamine, histidine, leucine, methionine, phenyl alanine, proline and lysine in all the treated groups. The decrease amino acids reflect the hypoxic stress affected the lung tissues as detected by increased fibrosis of maternal lung and hyperplasia and necrotic foci in newborn rats [40].…”
Section: Discussionmentioning
confidence: 97%
“…Kim et al [40] reported a decrease of threonine, citrulline, histidine and tryptophan and increase in proline, isoleucine, phenylalanine and ornithine in lung of Korean cancer patients with advanced pulmonary disease showed inverse correlation with alanine, phenylalanine and tyrosine, however citrulline and tryphtophane were markedly changed in relation to energy intake [41].…”
Section: Discussionmentioning
confidence: 98%